Design Inquiry for AI Literacy Framework Development: Evidence from Indonesian Pre-service Primary School Teachers in Teaching English to Young Learners - Alpian Husna; Rika Setyawati; Audia Mecca (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Artificial intelligence (AI) has created new opportunities and challenges for teacher education, requiring pre-service teachers to develop competencies that support the responsible and pedagogically appropriate use of AI in classroom practice. This study identifies the educational needs that should inform the development of an AI literacy framework for Indonesian pre-service primary school teachers preparing to teach English to Young Learners (TEYL). The study employed a mixed-method Design Inquiry, operationalising the Analysis and Exploration phase of Educational Design Research. Quantitative data were collected through a questionnaire based on the UNESCO AI Competency Framework for Teachers (AI CFT); qualitative evidence came from semi-structured interviews, classroom observations, and document analysis. The findings revealed five educational needs: strengthening conceptual AI understanding, developing AI-enhanced pedagogy for TEYL, promoting human-centred and ethical AI practice, supporting continuous professional learning, and strengthening institutional support for AI literacy. These needs were translated into five design requirements, five core AI literacy competencies, and fifteen observable competency indicators, synthesised into an Empirical Design Requirements Matrix (DRM). The DRM is the principal outcome of this study: it links authentic educational evidence directly to design specifications for AI literacy framework development, providing an empirical foundation for constructing and validating a framework responsive to the needs of Indonesian pre-service primary school teachers.